Price setting behavior in an open economy and the determination of Finnish foreign trade prices - Hanna Freystätter (Bank of Finland, 2003)
This paper investigates price setting of internationally traded goods.We develop a theoretical model that incorporates sticky prices in the currency of both the buyer (local currency pricing) and seller (producer currency pricing).The nature of price setting is thus forward looking and the exchange rate effect depends on the relative share of local currency and producer currency pricing firms in the economy.The model is estimated with Finnish foreign trade, price data for the. period 1980-1998 The estimation results seem to support the model.The estimated share of local currency pricing is 40 percent, in the export sector and 60 percent, in the import sector implying that there is limited pass-through from exchange rate to destination- country prices in both sectors.
URN:NBN:fi:bof-201408071710
Keywords: 330; local currency pricing; producer currency pricing; GMM; Finnish foreign trade prices